Colloid flow in a horizontal cell subjected to heating from sidewall - Cherepanov, Ivan Nikolaevich (Computational Continuum Mechanics, 2016)
The influence of sedimentation on the convective flow of colloidal liquids filling a horizontal cell subjected to heating from sidewall is considered. The system of nonlinear equations is solved by the finite-difference method using explicit schemes. Three convective modes differing in the spatial structure and temporal behavior are distinguished. The transition between modes is accompanied by a jump in a dimensionless heat flux. Bifurcation diagrams for convective regimes are given. It is shown that at low temperature gradient there is a weak movement of a colloidal suspension, whose intensity is a few orders of magnitude smaller than that of the flow in a homogeneous fluid at equal parameters. In the flow of weak intensity, the concentration is redistributed so that the density gradient becomes substantially vertical, and the heat flux across the layer is absent. The transition from weak to strong current proceeds abruptly. A relationship between the threshold of transition from weak to intensive flow and the Boltzmann number characterizing the degree of gravitational stratification is determined. Another three-roll flow with intermediate intensity occurs as the Rayleigh number decreases. Stream-function and concentration fields are obtained for all the types of flows.